Improving the Financial Performance of MSMES: The Role of Financial Literacy and Behavior Through Financial Planning - Muh. Amrih; Ifadhila; Yunarti (Cv. Syntax Corporation Indonesia, 2026)
To provide a foundation for smarter financial strategies and policies for MSME owners, this study analyzes the effects of financial literacy and behavior on business performance in Pangkep Regency, focusing on financial planning as a mediator. The study concludes that financial literacy and behavior have an indirect positive impact on MSME performance through financial planning, a result that underscores the commonly ignored gap between knowledge and action. This study provides an alternative approach to MSME financial management by showing that actual financial behavior matters more to outcomes than knowledge alone, supported by behavioral finance frameworks and the Theory of Planned Behavior. Such conclusions back the implementation of empowerment programs and advanced technology for recording transactions. To test these causal relationships, this explanatory quantitative project surveys 358 MSME actors in Pangkep Regency using a 5-point Likert questionnaire, evaluating the structural and measurement systems through PLS-SEM and validating hypotheses with bootstrapping techniques. The study reveals that financial literacy and behavior contribute positively to financial planning, while financial behavior also maintains a direct link to MSME success. Financial literacy holds an indirect relationship with performance, mediated by financial planning, which elevates both operational effectiveness and planning standards. A key limitation is that the results center entirely on MSMEs within Pangkep Regency, meaning they lack wide generalizability. However, the study remains useful for guiding practitioners and policymakers as they create empowerment schemes meant to strengthen financial management through improved literacy, behavior, and planning habits.